2010
DOI: 10.1111/j.1949-8594.2009.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Instruction on Preservice Teachers' Knowledge of Fraction Operations

Abstract: This study determines whether web‐based instruction (WBI) represents an improved method for helping preservice teachers learn procedural and conceptual knowledge of fractions.. The purpose was to compare the effectiveness of web‐based instruction (WBI) with the traditional lecture in mathematics content and methods for the elementary school course. The results of this study suggest that the use of WBI in learning fractions is more effective. When compared with the traditional instruction, the WBI treatment res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
1
13
0
3
Order By: Relevance
“…Our review located only two studies that employed delayed post-testing to determine long-term retention effects of virtual manipulatives as a treatment (Clements, et al, 2001;Lin, 2010). Clements et al reported that scores of the group using Logo geometry software increased significantly from the previous test to the delayed test, while the scores of students in traditional instruction decreased.…”
Section: Design Methods Used In Previous Research On Manipulativesmentioning
confidence: 99%
“…Our review located only two studies that employed delayed post-testing to determine long-term retention effects of virtual manipulatives as a treatment (Clements, et al, 2001;Lin, 2010). Clements et al reported that scores of the group using Logo geometry software increased significantly from the previous test to the delayed test, while the scores of students in traditional instruction decreased.…”
Section: Design Methods Used In Previous Research On Manipulativesmentioning
confidence: 99%
“…Nguyen ve Kulm (2005) web tabanlı uygulamanın, öğrencilerin öğrenme süreçleri üzerindeki etkilerini ve katkılarını geleneksel uygulamalarla karşılaştırdığı deneysel çalışmada web tabanlı öğrenme süreci geçiren grubun hem kesir hem de ondalık işlemler için daha iyi performans gösterdiği sonucuna ulaşmışlardır. Lin (2009) öğretmen adaylarının kesir bilgisine ilişkin web tabanlı öğretimin ve geleneksel öğretim yöntemlerinin karşılaştırmalı etkinliğini araştırmıştır. Deney ve kontrol gruplu deneysel desende yürütülen çalışmada öğretmen adaylarının kesir kavramları ile ilgili Web tabanlı kaynaklarla ders verdikleri zaman kavramsal anlayışlarını geliştirme fırsatı sağladıkları ve etkili bir yöntem oluşturduğu sonucuna ulaşılmıştır.…”
Section: Introductionunclassified
“…Gelişen teknoloji de web tabanlı öğrenme ortamlarını matematik eğitimi için daha somut, anlaşılır ve problem çözmeye uygun hale getirmiştir. Lin (2009), matematiksel kavramları yapılandırmada interaktif internet kaynakları yoluyla görsel modeller ve animasyon gösterimleri kullanımının önemli bir etkisinin olduğunu belirtmiştir. Bu sebeplerden dolayı matematik öğretmenlerinin web tabanlı uzaktan eğitim hakkındaki görüşlerini incelemek önemlidir.…”
Section: Introductionunclassified
“…During the past decades, computers have been used as learning tools in education. Computer-assisted instruction provides a better learning environment in education (Lin, 2009). In Thailand, the Basic Education Core Curriculum of the Ministry of Education encourages teaching and learning English or other subjects using ICT, especially in learning English.…”
Section: Computer Assisted Instructionmentioning
confidence: 99%